Federative Republic of Brazil - Social Insurance and Labor Supply : Assessing Incentives and Redistribution - World Bank (Washington, DC, 2013)
This technical report analyzes the potential effects of the pensions and income protection systems on labor supply decisions and through this channel the coverage and cost of the programs. The report addresses five policy questions: (i) how is the pension system influencing decisions regarding entry into the labor market, sector choice (formal/informal), and retirement? (ii) How are current income protection programs affecting turnover; job search efforts and sector choice?; (iii) Are there interactions between the two systems that aggravate or mitigate incentive effects?; (iv) What is the role of redistributive policies in determining observed outcomes?; and (v) Are there policy interventions that could be considered to correct incentives, while securing adequate income protection for different population groups (including workers in the informal sector)? The report is organized in three sections. This first section discusses the motivations for the study and sets the context by briefly describing some key stylized facts about the Brazilian labor market. The focus is on the composition of the labor force, its distribution by occupational categories, unemployment risks, and transitions between employment states including workers flows between the formal and informal sectors. The second section analyzes the Brazilian social insurance system in terms of incentives and redistribution. It starts with an overview of institutional arrangements, programs, and financing mechanisms, which flags the problem of a high tax-wedge. The report then analyzes the rules of the pensions and income protection systems and their potential effects on behaviors. The final section proposes a policy framework to guide reforms that could 'correct' incentives by making redistribution more transparent and progressive. A behavioral life-cycle model estimated for Brazil is used to illustrate how the application of this framework could affect contribution densities (and therefore the time spent working in formal sector jobs), retirement ages, savings, and programs cost. A companion policy note on social insurance and labor supply summarizes the main conclusions and recommendations from the analysis.